The Spread of Chaoshan Food Culture in Pontianak: 潮汕饮食文化在坤甸的传播 - Aretha, Paula (Mandarinable: Journal of Chinese Studies, 2024)
"Food is the first necessity of the people" illustrates the importance of diet in people's lives. Food is closely related to everyone's life. Food is closely related to everyone's life, it affects the survival of each ethnic group and forms the cultural essence of that ethnic group. "Chaoshan cuisine is the best in the world", the unique taste makes Chaoshan cuisine famous all over the world, and enjoys the honor of "the hometown of Chaoshan cuisine". When hipsters go overseas to make a living, they still maintain their original food customs and hobbies. Pontianak City, West Kalimantan, Indonesia, is one of the cities where Chaoshan people immigrate and live more, and it still retains a strong Chaoshan culture, and we can still find a lot of Chaoshan cuisine in Pontianak's Chinatown, and Chaoshan cuisine accounts for most of Pontianak's food culture. With the mountains and the sea in the backdrop of the mountains, and the longest river in Indonesia, Sungai Kapuas, running through the city, Pontianak has a pleasant climate, beautiful scenery and abundant products. Due to its unique wealth, the delicacies of the mountains and seas – a wide variety of seafood and other ingredients – provide a rich resource for people to cook delicious meals. Most of the Chinese in Pontianak are descendants of the Teochew people, so a food culture based on Teochew flavors has been formed - "Pontianak cuisine" that is derived from Teochew cuisine but is more distinctive than Teochew cuisine. But will all these Haitian food cultures change? This article will analyze and compare the methods mainly used in this study, followed by interviews and discussions with relevant people.